2002
DOI: 10.1002/qua.10277
|View full text |Cite
|
Sign up to set email alerts
|

When, in the context of drug design, can a fluorine atom successfully substitute a hydroxyl group?

Abstract: ABSTRACT:In this article, we deal with the question of whether a fluorine atom can substitute a hydroxyl group in such a way that will lead to a compound showing a desired biologic activity, that is, a potential new drug. It is obvious that a fluorine atom differs from a hydroxyl group, as it cannot donate hydrogen bonds. However, it can accept them. Moreover, both fluorine and oxygen are of similar size and are the most electronegative elements. Therefore, a fluorine atom is thought to be a good substitute fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 80 publications
1
15
0
1
Order By: Relevance
“…Liljefos proposed a bioactive conformation of a pheromone component using a 3D-QSAR study, [13] and Hoffmann and Rychlewski reported that the substitution of hydrogen by fluorine caused a significant modification of the favored conformer. [14] Here we report the results of our computational study and show that the modified conformational preference caused by the pointfluorination of eldanolide is consistent with a loss of EAG activity (Figure 1). …”
Section: Introductionsupporting
confidence: 69%
“…Liljefos proposed a bioactive conformation of a pheromone component using a 3D-QSAR study, [13] and Hoffmann and Rychlewski reported that the substitution of hydrogen by fluorine caused a significant modification of the favored conformer. [14] Here we report the results of our computational study and show that the modified conformational preference caused by the pointfluorination of eldanolide is consistent with a loss of EAG activity (Figure 1). …”
Section: Introductionsupporting
confidence: 69%
“…One important advantage of introducing fluoride is to render the compound relatively resistant to metabolic transformation due to the high energy of carbon-fluorine bond. 16 Unexpectedly, we found that compound 7 has significantly lower activity for CD22 (IC 50 5 μM; 50-fold less potent than 5 ). Obviously, a fluorine atom cannot donate hydrogen bonds, but it is electronegative and can accept them.…”
Section: Resultsmentioning
confidence: 63%
“…The rationale for such strategy stems from similarities between fluorine and oxygen in polarity and close isosteric relationship. 16 Consequently, a F atom is considered as a good substitute of a OH group. One important advantage of introducing fluoride is to render the compound relatively resistant to metabolic transformation due to the high energy of carbon-fluorine bond.…”
Section: Resultsmentioning
confidence: 99%
“…[20][21][22] The effect of substituting an F atom for an OH group has been widely studied by Hoffmann et al using the quantum chemical calculation. [23][24][25] In the case of L L-tartaric acid, replacement of an OH group by an F atom results in important conformational changes and ends up with greater conformational diversity, 23 while for D D-glucose, substitution of an F atom for an OH group does not change much the shape and the electrostatic properties of the molecule. Hence, potential drugs obtained by replacing an OH group by an F atom are more 0008 likely to be discovered with cyclic compounds than aliphatic ones.…”
Section: Introductionmentioning
confidence: 98%